The Synergy of the Strategy and the Targets on Water and Sanitation: Array - Cristea, Mandita (Acta Universitatis Danubius. Juridica, 2020)
The integration of sustainable development objectives in national development strategies and regulations to achieve Agenda of the year 2030, are the necessary means to the effective implementation of the 17 targets in a balanced way.In this paper, we have summarized the analysis of the Strategy for water supply and sanitation for 2014-2028 and to the National Development Strategy “Moldova-2030” in view of the integration of the Objective of Sustainable Development, no. 6 – “clean Water and sanitation”, the implementation of which depends on: the reduction of poverty, the ensuring of a healthy diet, the decrease in the rate of mortality and ill-health, access to energy resources and economic growth, adequate housing, sustainable communities. The research is based on the reports, the guidelines, the findings and recommendations developed in the framework of the project “Nationalization of the Agenda and the Sustainable Development of the Republic of Moldova”, a continuing study and analysis of the Strategy for water supply and sanitation National Strategy “Moldova, 2030” in order to identify the achievement of the synergies Target for the Development of the long-Lasting. 6, with the other goals and targets of the global. The methods of empirical analysis to reveal aspects of the blurry of a sustainable solution to the problems, while the criticism of the conclusions drawn can be used and further developed in future studies as a reference concept on the development of sectoral policies, strategies and plans of action.